ANALISIS MOTIVASI DAN HASIL BELAJAR WARGA BELAJAR PROGRAM KESETARAAN PAKET C DI PKBM NURUL FURQON - Nurhayati, Nurhayati; Hidayat, Dayat; Meilya, Ika Rizqi (IKIP Siliwangi, 2025)
This research aims to describe the analysis of motivation and learning outcomes of students in the Package C equality program at PKBM Nurul Furqon. This study uses a qualitative approach. The research subjects consist of one head of the PKBM, tutors or educators, and students. Data was collected through observation of learning activities, interviews, and documentation. The data analysis technique involved data reduction, data presentation, and conclusion drawing. In this study, there are indicators of learning motivation found in the students, namely: attitude, needs, stimulation, affection, and reinforcement. The students also demonstrated learning outcomes during and after the learning process based on indicators of the cognitive, affective, and psychomotor domains. The motivation and learning outcomes of the students influenced them during their participation in the Package C equality program, shaping their current personalities.